1980
DOI: 10.2337/diab.29.2.132
|View full text |Cite
|
Sign up to set email alerts
|

Short-term Regulation of Insulin Receptor Affinity in Man

Abstract: We have studied the short term regulation of insulin receptors by serially measuring insulin binding to erythrocytes during 5 h of infusions of glucose and insulin. Two infusion protocols were employed: (1) Hyperinsulinemic study. Subjects were infused with insulin (80 mU/min) to induce sustained hyperinsulinemia, while euglycemia was approximated by infusion of glucose (8 mg/kg/min). (2) Hyperglycemic study. Subjects were infused with glucose (7 mg/kg/min) and a small amount of insulin (10 mU/min), while endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
24
0

Year Published

1981
1981
1996
1996

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(32 citation statements)
references
References 0 publications
8
24
0
Order By: Relevance
“…Similarly, muscle cells from experimentally hypoinsulinemic diabetic mice (4) and rats (5) display increased insulin binding. The observation in all three tissues is compatible with the widely accepted hypothesis of regulation of insulin receptors by ambient insulin concentration in vitro (6) and in vivo (7).…”
supporting
confidence: 74%
See 1 more Smart Citation
“…Similarly, muscle cells from experimentally hypoinsulinemic diabetic mice (4) and rats (5) display increased insulin binding. The observation in all three tissues is compatible with the widely accepted hypothesis of regulation of insulin receptors by ambient insulin concentration in vitro (6) and in vivo (7).…”
supporting
confidence: 74%
“…Blood samples (0.1 ml) were taken at times 1, 2,3, 5,6,7,8,10,15,20,25,30,35,40,45,50,55, and 60 min after injection. Total "4C-radioactivity and the concentration of intact [3H]insulin were then determined, the two isotopes being detected simultaneously in the scintillation counter.…”
Section: Initial Distribution Volume As Determined By [3h]insulin Andmentioning
confidence: 99%
“…The recent observation (6) that human postglucose serum stimulates the insulin effect on rat adipocytes favors the latter hypothesis. It is unlikely that plasma glucose or insulin are such factors, because Insel and his colleagues (23) have shown that a 3-h infusion of insulin or glucose does not alter insulin receptor binding in man.…”
Section: Resultsmentioning
confidence: 99%
“…When competition data for the three groups were subjected to Scatchard analysis (Scatchard, 1949), plots were curvilinear and parallel to each other (Fig. 4) (Insel et al, 1980;Kobayashi et al, 1978). Scatchard analysis of the binding curves revealed that the change in insulin binding to erythrocytes was associated with an alteration in the insulin receptor concentration.…”
Section: Group B Was Between the Groupmentioning
confidence: 99%